Akurasi Citra Data Foto Udara UAV Quadcopter Persimpangan Lalu Lintas Kota Kendari - La Ode M. Nurrakhmad Arsyad; Statiswaty Statiswaty; Laode M. Iradat; M. Yamin; Try Sugiyarto (Rekayasa Sipil, 2020)
The use of the Unnamed Aerial Vehicle (UAV) called “Drone” has been widely used in various areas of planning, one of them by mapping the highway traffic junction. The range of remote roaming, adjustable spatial resolution greatly gives flexibility in the effectiveness of field surveys. The mapping accuracy test conducted on 7 (seven) Unsignaling junction in Kendari City by Omisi and Komisi Equation method gives significant output and quite accurate to serve as further planning data. The difference between image and field measurement results, obtained accuracy of 96%, so that the use of UAV in supporting mapping, survey and field planning still prioritize effectiveness and accuracy of the measurement.